Pharmacology of P2X Receptors and Their Possible Therapeutic Potential in Obesity and Diabetes - Guillermo A. Cabral-García; José R. Cruz-Muñoz; Eduardo E. Valdez-Morales; Alma Barajas-Espinosa; Andrómeda Liñán-Rico; Raquel Guerrero-Alba (MDPI AG, 2024)
The role of P2X ionotropic receptors in the behavior of purinergic signaling on pathophysiological processes has been widely studied. In recent years, the important participation of P2X receptors in physiological and pathological processes, such as energy metabolism, characteristic inflammatory responses of the immune system, and nociceptive activity in response to pain stimuli, has been noted. Here, we explore the molecular characteristics of the P2X receptors and the use of the different agonist and antagonist agents recently described, focusing on their potential as new therapeutic targets in the treatment of diseases with emphasis on obesity, diabetes, and some of the complications derived from these pathologies.